Financial Technology Analysis for MSMEs Based on Sharia Peer To Peer Lending - Suliyati; Dian Febriyani; Mahfud; Jamaluddin (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
This research is aligned with the advancement of Financial Technology (FinTech) in Indonesia. FinTech provides a convenient option for the general public to carry out financial transactions online, including meeting the financial needs of Micro, Small, and Medium Enterprises (MSMEs). One of the challenges faced by MSMEs is difficulty in accessing traditional financial institutions. This problem can be resolved through the advancement of FinTech in Indonesia, namely through the establishment of FinTech Shariah as a startup that offers a platform for connecting funders and entrepreneurs seeking money using the sharia system. This research methodology employs qualitative descriptive research by observing the website of a FinTech Peerto-Peer (P2P) lending company in Indonesia, specifically focusing on seven companies listed in the Financial Services Authority. Additionally, interviews with UMKM (Micro, Small, and Medium Enterprises) are conducted to gather information pertaining to the utilization of Sharia-compliant FinTech by MSMEs. The research findings revealed that out of the 50 informants who were thoroughly analyzed, only 2% utilized Fintech peer-to-peer lending shariah as their corporate lending institution. Additionally, the majority of the informants were unaware of and lacked understanding regarding the application of fintech peer-to-peer lending shariah for their corporate financing needs. There should be a boost in Sharia FinTech financial literacy for MSMEs in order for them to fulfill their financing requirements through Sharia Fintech Peer-To-Peer Lending (P2P).